Hereditary predisposition to malignant myeloid hemopathies: Caution in use of saliva and guideline based on our experience - Perani, Alexandre; Bourthoumieu, Sylvie; Rizzo, David; Chauzeix, Jasmine; Dauriat, Benjamin; Turlure, Pascal; Girault, Stéphane; Veyrune, Léa; Roubinet, Maxime; Feuillard, Jean; Yardin, Catherine; Gachard, Nathalie (Frontiers in Oncology, 2023)
Predisposition to myeloid malignancies is a field at the border of hematology and genetics. Knowledge in this domain have so rapidly increased that WHO defined in 2016 the new “Myeloid Neoplasms with Germline Predisposition” category of tumors. High throughput sequencing is frequently performed in tumors either for diagnosis or prognosis, but this approach may identify potential germline variants that have to be confirmed on non-infiltrated tissues. In this study, we systematically compared NGS data from genetic analysis performed on all sample types (bone marrow, blood, saliva, skin fibroblasts and hair follicles) in 29 patients, and 44 of their relatives (blood and saliva). Results showed that saliva was usable for relatives, but only for 24% (7/29) of our patients. Most of patients’ saliva were either “non-contributive” (14/29 i.e., 48% because clearly or probably infiltrated) or “inconclusive” (8/29 corresponding to 28%). The recommendations for the use of saliva we present here focus on the importance of collecting saliva during remission when possible. Moreover, we propose hair follicles as an alternative to skin biopsy, that remains the gold standard especially in case of allogenic hematopoietic stem cells transplantation. Technological progresses have revolutionized the diagnosis of predisposition to solid or hematological malignancies, and it is very likely that new techniques will help to manage the familial predisposition in the future.